Innovation in Smart Fencing with Internet of Things (IoT) Technology for Ease of Use - Salamah, Irma; Rahmika, Rahmika; Nurdin, Ali (Prahasta Publisher, 2023)
The fence is a structure that is deliberately designed to limit or protect the house. The fence serves to provide protection or block views so that the house becomes safer. It is usually pushed manually by hand to open and close the fence. This is considered very inconvenient and time-consuming. This problem underlies the idea of creating an automatic fence opening and closing system using a smartphone by utilizing Internet of Things (IoT) technology in order to facilitate human work to open and close the fence. A smartphone is used as a NodeMCU controller contained in the ESP8266 WiFi module via an internet connection to connect to the Android Studio application. To move the fence using an electric motor as the driving force which is connected directly to NodeMCU. When the fence opens and closes, the relay will regulate and activate to give orders to the electric motor to move the fence. The fence will stop when the switch opens and the switch close responds, the motor will stop moving. Realtime data results are stored in Firebase and the results of this design are expected that all components are connected properly so that automatic fences can be used.